Data protection and privacy in healthcare : research and innovations - Elngar, Ahmed A.; Pawar, Ambika; Churi, Prathamesh (Boca Raton, FL : CRC Press, 2021)
"The Healthcare industry is one of the largest and rapidly developing industries. Over the last few years, healthcare management is changing from disease centered to patient centered. While on one side the analysis of healthcare data plays an important role in healthcare management, but on the other side the privacy of a patient's record must be of equal concern. This book uses a research-oriented approach and focuses on privacy-based healthcare tools and technologies. It offers details on privacy laws with real-life case studies and examples, and addresses privacy issues in newer technologies such as Cloud, Big Data, and IoT. It discusses the e-health system and preserving its privacy, and the use of wearable technologies for patient monitoring, data streaming and sharing, and use of data analysis to provide various health services. This book is written for research scholars, academicians working in healthcare and data privacy domains, as well as researchers involved with healthcare law, and those working at facilities in security and privacy domains. Students and industry professionals, as well as medical practitioners might also find this book of interest"--
OCLC-licensed vendor bibliographic record.
Keywords: Medical care -- Data processing; Data protection; COMPUTERS / Database Management / Data Mining; TECHNOLOGY / Manufacturing; COMPUTERS / Data Transmission Systems / General